Huwe1 supports B-cell development, B-cell-dependent immunity, somatic hypermutation and class switch recombination by regulating proliferation - Spanjaard, Aldo; Stratigopoulou, Maria; de Groot, Daniël; Aslam, Muhammad; van den Berk, Paul C. M.; Stappenbelt, Chantal; Ayidah, Matilda; Catsman, Joyce J. I.; Pardieck, Iris N.; Kreft, Maaike; Arens, Ramon; Guikema, Jeroen E. J.; et al. (Frontiers in immunology, 2023)
The development and differentiation of B cells is intimately linked to cell proliferation and the generation of diverse immunoglobulin gene ( Ig ) repertoires. The ubiquitin E3 ligase HUWE1 controls proliferation, DNA damage responses, and DNA repair, including the base excision repair (BER) pathway. These processes are of crucial importance for B-cell development in the bone marrow, and the germinal center (GC) response, which results in the clonal expansion and differentiation of B cells expressing high affinity immunoglobulins. Here, we re-examined the role of HUWE1 in B-cell proliferation and Ig gene diversification, focusing on its involvement in somatic hypermutation (SHM) and class switch recombination (CSR). B-cell-specific deletion of Huwe1 resulted in impaired development, differentiation and maturation of B cells in the bone marrow and peripheral lymphoid organs. HUWE1 deficiency diminished SHM and CSR by impairing B-cell proliferation and AID expression upon activation in vitro and in vivo , and was unrelated to the HUWE1-dependent regulation of the BER pathway. Interestingly, we found that HUWE1-deficient B cells showed increased mRNA expression of Myc target genes upon in vitro activation despite diminished proliferation. Our results confirm that the E3 ligase HUWE1 is an important contributor in coordinating the rapid transition of antigen naïve, resting B cells into antigen-activated B cells and regulates mutagenic processes in B cells by controlling AID expression and the post-transcriptional output of Myc target genes.